Patterns of information sources used by graduate students: A citation analysis of doctoral dissertations in the field of Islamic studies - Abdullah, Raihanah; Ab Rahman, Asmak; Kamri, Nor Azzah (2014)
This article depicts the results of a study carried out to ascertain the information pattern based on the sources used by graduate students from the Islamic Studies Academy submitted at the University of Malaya, Kuala Lumpur. A total of 14377 citations consisting of 54 doctoral dissertations from the Year 2005 to 2009 were examined using the citation analysis. The highest citations per dissertation was 684, while the lowest being 105 citations. The result shows that the materials used by graduate students in this field vary and are multidisciplinary by nature. Books were cited more than other forms of sources contributing 65%, where journal articles contributed 20%.Conference proceedings contributed 11%, dissertations and thesis 3% and other categories consisted of web sites, interviews and legal documents contributing 9%. These findings corroborate with previous citations done in the Humanities discipline. Among the most popular cited journals are in-house journals namely Jurnal Syariah and Jurnal Usuluddin. In addition, graduate students used a substantial amount of Malaysian language sources at the rate of 60%, Arabic language scholarships contributed to 40% of the total citations. Approximately 30% of all sources cited are over 10 years of age. Hence, this study provides valuable insights to guide librarians in understanding the sources used and serves as an analytic tool for the development of source collection in the library services.